2018
DOI: 10.1016/j.soilbio.2018.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality alters drivers of soil enzyme activity in subalpine grassland soil undergoing climate change

Abstract: In mountain ecosystems with marked seasonality, climate change can affect various processes in soils, potentially modifying long-term key soil services via change in soil organic carbon (C) storage. Based on a four-year soil transplantation experiment in Swiss subalpine grasslands, we investigated how imposed climate warming and reduced precipitation modified the drivers of soil carbon enzyme potential activities across winter and summer seasons. Specifically, we used structural equation models (SEMs) to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In our study, the seasonal patterns in soil microbial biomass were strongly dependent on elevation and incubation year (Figure 3 and Figure S2), suggesting ecosystem‐ and year‐specific effects on seasonal changes in soil microbial biomass (Birgander et al, 2014; Siles et al, 2016). It could be attributed to the spatial and temporal heterogeneity and their synergistic effects of the crucial drivers of seasonal changes in soil microbial biomass (Fu et al, 2020; Puissant et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the seasonal patterns in soil microbial biomass were strongly dependent on elevation and incubation year (Figure 3 and Figure S2), suggesting ecosystem‐ and year‐specific effects on seasonal changes in soil microbial biomass (Birgander et al, 2014; Siles et al, 2016). It could be attributed to the spatial and temporal heterogeneity and their synergistic effects of the crucial drivers of seasonal changes in soil microbial biomass (Fu et al, 2020; Puissant et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This temperature-enzyme activity relationship has historically been modelled with the Arrhenius law, although recently proposed models better represent the experimentally observed bell-shaped response curve (Alster et al, 2020). Concurrently, other climatic variables also impact enzyme functioning, for instance, changes in soil moisture alter substrate diffusion and the likelihood of substrate-enzyme encounters and the production of microbial extracellular enzymes, ultimately leading to changes in enzyme activity, as observed for the extracellular beta-glucosidase enzyme, a key player in soil organic carbon decomposition (Puissant et al, 2015(Puissant et al, , 2018Wallenstein & Weintraub, 2008;Zhang et al, 2011). Changes in microclimate can also affect substrate concentration, such as an increase in CO 2 concentrations that enhance the activity of the photosynthetic enzyme Rubisco (Galmés et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that although distinct variations in plant community composition were observed during different seasons under warming conditions, the microbial communities were similar (Slaughter, Weintraub, & McCulley, 2015). Puissant et al (2015, 2018) reported that changes in soil microbial community composition are not linked to the seasonal dynamics of soil carbon under climate change manipulation. Another study indicated that microbial responses to warming rely on precipitation, which only occurs during non‐drought seasons (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%